Vertical distributions of 226Ra, 228Ra, and 137Cs activities in the southwestern part of the Sea of Okhotsk - Hamajima Y.; Kofuji H.; Nagao S.; Minakawa M.; Yoshida K.; Inoue M.; Yamamoto M. (EPJ Web of Conferences, 2012)
We collected 14 water column seawater samples in the southwestern part of the Sea of Okhotsk and employed low-background γ-spectrometry with convenient minimal radiochemical processing to determine the activities of 226Ra (half-life t1/2 = 1600 y), 228Ra (5.75y), and 137Cs (30.2 y) of the samples. All of these nuclides exhibited unique vertical profiles; 226Ra, 228Ra, and 137Cs activities exhibit small variations from 50–500 m depth (226Ra, ~ 2 mBq l−1; 228Ra, ~0.4 mBq l−1; 137Cs, ~ 1 mBq l−1); These profiles can be explained by convective mixing of surface water to this layer.